(untitled) (Journal of the College of Education for Women, 2019)
The feature that prevails in spoken political discourse - especially with regards to the factthat it is otherwise used in the written one - is relatively high degree of formality. It is then justlogical that formality is usually accompanied with more polite forms and higher degree ofimpersonality. Such discourse is characterized by the choice of specific vocabulary and syntacticstructures as well. However, there are some tendencies to bring political speech nearer to theeveryday discourse and that is why political speeches have been becoming more informal andpersonal. Like any other types of discourse, the American political speeches are loaded withdeictic expressions that form an essential complementary part of any text.The present paper aims at presenting a full presentation of the concept of deixis in generaland the discourse deixis in particular. This presentation is the subject matter of the first andsecond sections of the paper. In the third section discrimination is drawn between twooverlapping concepts: discourse deixis and anaphora.The main aim of the present paper is to investigate the discourse deixis in the Americanpolitical speeches, as a type of institutional talk, to find out the way this linguistic phenomenonused in the American political speeches and to see whether there is a special strategy for the useof the discourse deixis in this type of text. To achieve this aim, three American political speecheshave be downloaded randomly from the internet from the websiteofhttp://www.americanrhetoric.com/speeches/wariniraq,and analyzed carefully. Each speech isdelivered by a different politician; the first is for Barak Obama, the second is for CondoleezzaRice, and the third is for Paul Bremer. The analysis of the discourse deixis represents thepractical part of the paper which is introduced in section four. The practical part also includes anumber of conclusions which the analysis has come with.